Perancangan Sistem Informasi Administrasi Pembayaran SPP Siswa SMP Bunga Bangsa 4 Medan Berbasis Web - Sari, Dewi Purnama; Simamora, Roni J.; Saragih, Rijois Iboy E. (Universitas Methodist Indonesia, 2024)
The development of information technology has become a primary necessity in human life and has a significant impact on various institutions, including educational institutions. However, at SMP Swasta Bunga Bangsa 4 Medan, the student tuition payment system (SPP) is still manual, leading to inefficiency, lack of data security, and difficulties in checking bills. Therefore, a web-based information system needs to be developed to address these issues and enhance the performance of the administrative staff. The aim of this research is to design a web-based SPP payment information system to assist in the student tuition payment process. The benefits include providing payment information, facilitating transaction records, and enhancing data security.